Exploiting important horticultural and quality traits of some traditional pepper genotypes - Chouikhi, Marwa; Ilahy, Riadh; Tlili, Imen; R him , Thouraya (Journal of Postharvest Technology, 2023)
Worldwide pepper (Capsicum annum L.) is considered one of the most important vegetable crops grown and consumed. It is widely recognized that peppers pods synthesize and store a wide array of bioactive phytochemicals beneficial for human health such as vitamins A, C and E, as well as phenolic, flavonoids, carotenoids and capsaicinoids with well-known antioxidant properties. It has been reported that the levels of these compounds vary depending on various factors such as genotypic differences, pre- and post-harvest agricultural practices. Besides, although, processing industries widely use in their product mostly hybrid cultivars, recently, the interest of consumers has been shifted towards local/traditional cultivars of peppers for their low input/water demand, particularly under the ongoing climatic change context, associated to their high nutritional value. Therefore, in this study, four local pepper genotypes consisting of (Baklouti, Beldi, Kairouan and Nabeul) were compared for their main horticultural traits and vitamin C content. The result revealed significant differences affecting most of the tested attributes. The highest plant height was recorded for the cultivars Nabeul and Kairouan (119.67 cm) and the lowest for the variety Baklouti (66 cm). Added to this, the highest plant cover area was recorded for the cultivars Nabeul (39 cm) and the lowest for the variety Baklouti (19 cm). Kairouan showed the highest yield (1841, 66 g/plant) while Baklouti showed the lowest (1644, 08 g/plant). Average fruit weight varied from 37.75 g in cultivar Kairouan to 34.33 g in Beldi variety. The highest SPAD index was recorded for the cultivar Beldi (62.97) and the lowest for the variety Kairouan (47.8). Besides, the highest chlorophyll fluorescence was recorded for the cultivar Beldi (0.77) while Baklouti showed the lowest (0.72). It is also worthy to underline that in this experiment, no blossom end rot symptoms were noticed in all genotypes. Vitamin C content, Brix and pH varied also significantly in the different pepper genotypes. Cultivar Beldi exhibited the highest vitamin C content (39,73 mg/g fw) and the lowest was recorded for Kairouan (18,13 mg/fw). Titratable acidity varied from 0.51% in cultivar Nabeul to 0.34% in Beldi.